2006
DOI: 10.1158/0008-5472.can-06-1996
|View full text |Cite
|
Sign up to set email alerts
|

β2-Microglobulin Is a Signaling and Growth-Promoting Factor for Human Prostate Cancer Bone Metastasis

Abstract: The protein factor B2-microglobulin (B2M), purified from the conditioned medium of human prostate cancer cell lines, stimulated growth and enhanced osteocalcin (OC) and bone sialoprotein (BSP) gene expression in human prostate cancer cells by activating a cyclic AMP (cAMP)-dependent protein kinase A signaling pathway. When B2M was overexpressed in prostate cancer cells, it induced explosive tumor growth in mouse bone through increased phosphorylated cAMPresponsive element binding protein (CREB) and activated C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
113
0
3

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 104 publications
(121 citation statements)
references
References 43 publications
5
113
0
3
Order By: Relevance
“…Selective activation of CREB could promote local tumor growth and distant metastasis (Huang et al, 2006;Melnikova et al, 2006). Many modulators of CREB activity are abundant in bone tissues, such as stromal cell-derived factor-1, fibroblast growth factor, transformation growth factor (Johannessen et al, 2004) and b-2-microglobulin (Huang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Selective activation of CREB could promote local tumor growth and distant metastasis (Huang et al, 2006;Melnikova et al, 2006). Many modulators of CREB activity are abundant in bone tissues, such as stromal cell-derived factor-1, fibroblast growth factor, transformation growth factor (Johannessen et al, 2004) and b-2-microglobulin (Huang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…In human prostate cancer (PCa), CREB may promote acquisition of neuroendocrine differentiation, associated with androgen-independent progression (Chen et al, 1999;Deeble et al, 2001). Previous studies from our laboratory and others indicated that CREB signaling regulated osteomimicry in PCa bone metastasis, conferring tumor survival and growth advantages in the bone microenvironment (Huang et al, 2006). Our results demonstrated that b-2 microglobulin activation of protein kinase A (PKA)-CREB signaling resulted in increased expression of osteocalcin and bone sialoprotein and conferred explosive PCa growth in bone.…”
Section: Introductionmentioning
confidence: 99%
“…27 In brief, three groups of six mice each were inoculated subcutaneously with 5 Â 10 6 A549 cells in 200 ml of phosphate-buffered saline at a single dorsal site. After 2 weeks, the tumor-bearing mice were treated with an intratumoral injection every 2 days for 2 weeks as follows: the group 'control', 20 ml of sterilized 0.9% (w/v) NaCl solution for each mouse; group 'NC', 0.8 mg of nonspecific scramble siRNA mixed with 19.2 ml of Lipofectamine2000 for each mouse; and group 'si', 0.8 mg of PC4 specific siRNA mixed with 19.2 ml of Lipofectamine2000 for each mouse.…”
Section: Tumor Model In Nude Micementioning
confidence: 99%
“…2-m has been reported by our laboratory and others to be a growth-stimulating factor and cell signaling molecule in several types of cancer cells [30][31][32][33]. We reported that 2-m played multiple roles in cancer development and mediates tumorigenesis, angiogenesis, and osteomimicry [30,31,34].…”
Section: Introductionmentioning
confidence: 69%